2010
DOI: 10.1111/j.1753-6405.2010.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

The increasing cost of healthy food

Abstract: Australians, no matter where they live, need access to affordable, healthy food. Issues of food security in the face of rising food costs are of concern particularly in the current global economic downturn. There is an urgent need to nationally monitor, but also sustainably address the factors affecting the price of healthy foods, particularly for vulnerable groups who suffer a disproportionate burden of poor health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
65
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 4 publications
7
65
0
Order By: Relevance
“…Importantly, self-efficacy is considered the most important precursor to behaviour change (42) . In addition, by taking their meals home, they included the family unit into the food work processes, providing the family an opportunity to sample new and healthier foods and to discuss important factors such as cost, preferences, dietary patterns and habits (8)(9)(10)(11)(12)(13) that had the potential to influence dietary change, which is important in the prevention of nutritionrelated disease (40,43,44) . Compared with other countries of the world, Australia is classified as 'food secure' (45) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, self-efficacy is considered the most important precursor to behaviour change (42) . In addition, by taking their meals home, they included the family unit into the food work processes, providing the family an opportunity to sample new and healthier foods and to discuss important factors such as cost, preferences, dietary patterns and habits (8)(9)(10)(11)(12)(13) that had the potential to influence dietary change, which is important in the prevention of nutritionrelated disease (40,43,44) . Compared with other countries of the world, Australia is classified as 'food secure' (45) .…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to healthy eating and food security among Australian Indigenous families have been attributed to poor nutritional knowledge and cooking skills, budgeting issues, high food prices, ease of access to convenience foods, poor access to nutritious foods and large household numbers (8)(9)(10)(11) . This has resulted in poor nutrition throughout the life span, causing inadequate consumption of proteins, carbohydrates, fats, minerals, vitamins and micronutrients, which are all essential in maintaining biological and physiological health (11)(12)(13) . In this context the women Elders and leaders of an Aboriginal community in regional south-west Western Australia collaborated with the researchers to develop and implement a health promotion programme for their community.…”
mentioning
confidence: 99%
“…The neoliberal emphasis on family responsibility for the health and well-being of the child has generated a market of interventions targeting more disadvantaged families, including interventions to increase physical activity and limit sedentary activities such as television viewing and computer time, to improve dietary habits, to increase social skills and coping skills, and to prevent behaviours that may signal behavioural or mental health disorders, and, more recently, programs to build resilience, optimism, confidence and/or self-esteem (Durlak & Wells, 1997;Birch & Davison, 2001;Stice et al, 2006). At the same time, the disadvantaged family is vulnerable to the rule of the market, where studies point to the problem of food affordability, even in wealthy Western countries (Drewnowski & Darmon, 2005;Friel et al, 2006;Kettings et al, 2009), and indicate that the costs of healthier foods are rising more rapidly than the costs of less nutritious foods (Harrison et al, 2007(Harrison et al, , 2010Bums et al, 2008). These broader structural issues of social inequality underpin the persistence of health indices within modernity's paradox, as a study of a nutrition program in an Aboriginal community suggests:…”
Section: Parenting the Un/healthy Millennium Childmentioning
confidence: 97%
“…4 Although there is no routine food price monitoring system in Australia, 5 state-based surveys have examined the affordability of healthy food. 6,7 They have shown that the cost of healthy food has increased between 2000 and 2013 8,9 and that food costs more in remote areas, with fruit and vegetables the most expensive items. [10][11][12] The Australian Dietary Guidelines…”
mentioning
confidence: 99%
“…Even with the GST exemption, the cost of healthy foods has increased disproportionally to the consumer price index (CPI) and to unhealthy foods. 8,9 In economic terms, the GST is considered a regressive tax as it has a greater impact on lower income families. 25,26 This formed part of the decision to exempt these foods from the GST due to the greater proportion of income spent by low-income families on food.…”
mentioning
confidence: 99%